HOW AI IS CHANGING THE WAY STUDENTS LEARN - Dilmurodova Nilufar; Alimkhanova Nigorakhon Amilevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: This paper examines the growing influence of Artificial Intelligence (AI) on contemporary learning practices. It considers both the opportunities and the challenges associated with integrating AI into educational environments. Particular attention is given to personalized learning, the risk of over-reliance on AI tools, the evolving role of teachers, and concerns related data privacy. The paper argues that AI can significantly develop learning outcomes when it is used as a supportive tool that encourages active engagement rather than passive dependence.